Non-Wage Job Values and Implications for Inequality - Tobias Lehmann (Institute of Labor Economics (IZA), 2023)
I study inequality in job values, both in terms of wages and non-wage values, in Austria over the period 1996 to 2011. I show that differences in non-wage job value between firms are non-parametrically identified from data on worker flows and wage differentials. Intuitively, firms with high non-wage value attract workers without paying a wage premium. I study the distribution of job value among workers and find a positive correlation between wage and non-wage value. Inequality in job value is thus considerably greater than wage inequality, reflected in the standard deviation of job value being more than twice as large as the standard deviation of wage. Job value inequality increases between 1996 and 2011, although wage inequality remains constant. An important reason is that, over time, dispersion of rents offered by firms increases, while compensating differentials lose importance.
Keywords: E24; J31; J32; 330; inequality; amenities; worker heterogeneity; firm heterogeneity; on-the-job search; wage dispersion; matched employer-employee data